Factors Influencing Agricultural Diversification: The Case of Northern Bangladesh - Mamun, Md Mamunur Rashid; Md. Abu Sayed Mondol; Md. Sadekur Rahman; Tamara Jackson (Indian Journal of Extension Education, 2026)
Agricultural diversification has significant positive impacts, including generating more rural employment and higher incomes, creating new market opportunities, improving nutritional standards, and empowering women. However, due to socio-economic, psychological, communicational, technological, infrastructural, and climate aspects, farmers’ agricultural diversification decisions are poorly understood. The study aimed to measure the extent of agricultural diversification and the influence of selected factors on it in northern Bangladesh in 2024. A multi-stage sampling method was utilized to pick 348 participants from the northern districts of Kurigram, Thakurgaon, and Dinajpur in Bangladesh. Simpson’s Index of Diversity results indicate that 85.1% of farmers had low to medium agricultural diversification, with the overall diversification level in northern Bangladesh ranging from 0.534 to 0.665. The Multiple Linear Regression model reveals that decision-making ability, risk orientation, credit-seeking behavior, extension media contact, and market accessibility had a positive effect on agricultural diversification, whereas farm size was found to negatively influence the adoption of agricultural diversification. Based on these findings, it is recommended that extension agencies and policymakers consider these factors when designing and implementing agricultural diversification programs in northern Bangladesh. Further research is suggested to explore smallholder farmers’ preferences for agricultural diversification in the region.